Pandangan Ulama Nu Dan Muhammadiyah Terhadap Fenomena Pencabulan Anak Di Kota Probolinggo - Dwi Winarni, Nur Fadilah; Syaifuddin Romli, Ahmad (MAQASID, 2024)
This study examines the perspectives of Nahdlatul Ulama (NU) and Muhammadiyah scholars on the phenomenon of child molestation in Probolinggo City. Children, as the future generation, require special protection, especially from the increasing incidents of sexual violence. The study uses a qualitative approach with a case study method, where data was collected through in-depth interviews, document analysis, and observation. The findings show that both NU and Muhammadiyah scholars strongly condemn child molestation, viewing it as contrary to moral values and Islamic teachings. Both groups emphasize the importance of moral and religious education as the primary preventive measure and support strict legal enforcement against perpetrators. Although there are differences in approaches to handling cases, the perspectives of these two organizations complement each other in the prevention and management of child molestation. This study provides insights into the role of scholars in formulating policies and strategies that align with religious norms and societal values to protect children from sexual violence.